Fine needle aspiration cytology in the evaluation of patients with radiographically occult palpable breast abnormalities - Ajkay, Nicolas (Surgery, 2015)
BACKGROUND: Patients who present with radiographically occult palpable breast abnormalities represent a diagnostic challenge. We hypothesized that fine needle aspiration cytology (FNAC) would be an accurate method for diagnosing and excluding malignancy in these patients. METHODS: The records of all patients undergoing FNAC at our institution between 2010 and 2012 were queried. 173 patients with 175 palpable breast masses without an imaging correlate were included. RESULTS: Of 175 FNAC performed, 2 (1%) were malignant, 16 (9%) were suspicious, and 157 (90%) were benign (n = 75) or non-diagnostic (n = 82). All 16 suspicious FNAC had additional biopsy, of which 4 were malignant. FNAC led to the identification of 6 (3.4%) occult malignancies. At a median follow-up of 16.3 months, 1 patient within the benign cohort was found to have an incidental 2.5 mm cancer identified on reduction mammaplasty, which was unrelated to the index mass. The negative predictive value of FNAC in benign patients was 100%. CONCLUSION: FNAC detected malignancy in a small but significant percentage of patients with a palpable mass and negative breast imaging, while excluding carcinoma in the remaining patients. FNAC may be included in the evaluation of patients with radiographically occult palpable breast masses.